Distribución vertical de las aves Dendroica pityophila y Teretistris fernandinae(Passeriformes: Parulidae) en Pinar del Río, Cuba - Herminio Plasencia Vázquez, Alexis (2009)
The Yellow-Headed Warbler (Teretistris fernandinae) and the Olive-Capped Warbler (Dendroica pityophila) are two bird species that co-exist in Western Cuba. Their spatial distribution has not been studied. This study evaluated their vertical distribution in pine forests during 2007. Six field trips were conducted to the Tibisí pine groves, Minas de Matahambre, Pinar del Río, Cuba, to determine the differential use of forest strata, with the fixed-radio round parcel method. A total of 30 counting points were located in every forest formation. The forest stratum was recorded for each detected bird according to three categories: low stra-tum (0-2m over ground), medium stratum (2-6m) and high stratum (6m or more). From the 360 counts carried out, the Olive-Capped Warbler reached greater abundances (3.33±0.14ind/UM) than the Yellow-Headed Warbler (2.32±024ind/UM). No abundance differences were found among both forest formations. The Olive-Capped Warbler had the highest frequency in the high stratum and it was observed in the low stratum only during the reproductive season. The Yellow-Headed Warbler had a preference for the low and medium strata, and was seen less frequently in the high stratum.